Survival and causes of death in patients with alpha and beta-thalassemia in Northern Thailand - Adisak Tantiworawit; Thansita Kamolsripat; Pokpong Piriyakhuntorn; Thanawat Rattanathammethee; Sasinee Hantrakool; Chatree Chai-Adisaksopha; Ekarat Rattarittamrong; Lalita Norasetthada; Kanda Fanhchaksai; Pimlak Charoenkwan (Annals of Medicine, 2024)
AbstractBackground Thalassemia is the most prevalent hereditary anaemia worldwide. Severe forms of thalassemia can lead to reduced life expectancy due to disease-related complications.Objectives To investigate the survival of thalassemia patients across varying disease severity, causes of death and related clinical factors.Patients and methods We conducted a retrospective review of thalassemia patients who received medical care at Chiang Mai University Hospital. The analysis focused on survival outcomes, and potential associations between clinical factors and patient survival.Results A total of 789 patients were included in our study cohort. Among them, 38.1% had Hb H disease, 35.4% had Hb E/beta-thalassemia and 26.5% had beta-thalassemia major. Half of the patients (50.1%) required regular transfusions. Sixty-five patients (8.2%) had deceased. The predominant causes of mortality were infection-related (36.9%) and cardiac complications (27.7%). Transfusion-dependent thalassemia (TDT) (adjusted HR 3.68, 95% CI 1.39–9.72, p = 0.008) and a mean serum ferritin level ≥3000 ng/mL (adjusted HR 4.18, 95% CI 2.20–7.92, p < 0.001) were independently associated with poorer survival.Conclusions Our study highlights the primary contributors to mortality in patients with thalassemia as infection-related issues and cardiac complications. It also underscores the significant impact of TDT and elevated serum ferritin levels on the survival of thalassemia patients.